Deteksi Dini Dalam Perkembangan Sosial Emosional Anak - Anies Husnul. K.S; Ika Sulastri; Ismiyati Ismiyati (Universitas Muhammadiyah Klaten, 2025)
This study discusses the importance of detecting early childhood development. Early childhood social-emotional development is an important foundation in shaping personality, interaction skills, and readiness for future social life. Children with good social-emotional development will be better able to express their feelings, understand the feelings of others, and adapt to their social environment. The roles of family, educators, and the environment are crucial in supporting this development. This is an important step in quickly identifying any developmental deviations in children. Principles such as multidisciplinary involvement, consistency, and the use of appropriate assessment tools are essential components of this effort. Through early detection and intervention, children's potential can be optimized, and more complex developmental issues can be prevented. Early childhood development is a golden period in human life, marked by rapid growth across various aspects, including physical, motor, cognitive, language, social, and emotional development. This period is often referred to as the “golden age” because every stimulation a child receives during early childhood has a long-term impact on the quality of their life in the future. Therefore, attention to early childhood development from an early age is crucial to ensure optimal development in line with age-appropriate stages